(untitled) (Journal of Hama University, 2019)
This study aims to identify the impact of the financial structure on the profitability of Islamic banks, the study of the case of the International Islamic Bank of Syria during the period from 2010 to 2017. The importance of this study stems from the primary objective of banks in general, which is to maximize their profitability. This is one of The most important financial decisions related to the choice of structure of financial structure in banks. The descriptive approach was adopted. The simple regression method was used to summarize the relationship between the financial structure and the profitability ratios. The study model included an independent variable, the ratio of the financial structure, Assuming that there is no statistically significant effect between the independent variable (financial structure ratio) in the two dependent variables (return on assets and return on equity), based on the SPSS program, The results of this study showed that there is a statistically significant effect of the ratio of the financial structure in both return on assets and return on equity, and the relationship between them was positive.